Metabolism - Giacco A (Dynamic Media Sales Verlag, 2019)
The awareness that exercise is an essential means to maintain an adequate response to health challenges is increasing worldwide. Although whole body metabolism is governed by many organs that communicate to ascertain metabolic homeostasis, especially skeletal muscle is central in the response to metabolic changes, since it is the major site of glucose uptake and usage. Thus, metabolic diseases related to poor lipid/glucose handling due to over-nutrition and insufficient physical activity often trace back to muscle metabolic dysfunction, and vice versa. There is evidence that local thyroid hormone levels in muscle are crucial for the response to exercise, and that metabolically-active thyroid hormones can be considered possible exercise mimetics.Based on data obtained in rodents as well as humans, this short review aims to shedto light on why muscle metabolic integrity in response to exercise (increasingly studied in combination with restricted nutrition) is crucial for health, rangingfrom mechanistic aspects of muscle metabolism to the application of exercise to counteract dysfunction of metabolically-active tissues including liver and muscle itself. KEY WORDS: Exercise, Fasting, Insulin Resistance, Lipid Metabolism